The Implementation of BPHTB Tax with The E-BPHTB Application System that Applied on The Local Revenue Government of Lebak Regency - Bereukah Dinanti Putri; Mazda Eko Sri Tjahjono; Puspanita, Intan; Selly Anggraeni Haryono (PT Larva Wijaya Penerbit, 2024)
This study aims to find out the implementation process of the e-BPHTB application system on the Local Revenue Government of Lebak Regency and also to find out the obstacles that could hinder the implementation of the e-BPHTB application system. This study used a descriptive method with data collection techniques in the form of observation, documentation and descriptive. The samples of this study is Local Revenue Government of Lebak Regency. This study find out that the implementation of the e-BPHTB application system in the Local Revenue Government of Lebak Regency was accordance with existing regulations, the implementation of the e-BPHTB application system ease the PPAT/Notary Public and taxpayers in carrying out BPHTB tax reporting. There are obstacles in implementing the e-BPHTB application system, such as a lack of synchronization between the systems in Local Revenue Government of Lebak Regency and Bank as collecting agent and also the lack of optimal network at the Local Revenue Government of Lebak Regency that delay the process of inputting the taxpayer data